Latino high school graduation defying the odds - Romo, Harriett D.; Falbo, Toni (Univ. of Texas Press, 1996)
Romo and Falbo followed the school progress of 100 at-risk students in Austin, Texas, beginning in 1989 when the students were fifteen years old. Drawing on extensive interviews with the students and their parents, school records, and fieldwork in the students' schools and communities, the authors identify both the obstacles that cause many students to drop out and the successful strategies that other students and their parents pursue to ensure high school graduation. Detailed case studies allow students and parents to describe their experiences with the public schools in their own words
Keywords: High school dropouts -- United States -- Case studies; High school graduates -- United States -- Case studies; Mexican American high school students -- Social conditions -- Case studies; Youth with social disabilities -- Education (Secondary) -- United States -- Case studies; High school; Hispanos; Chicanos; USA; Fallstudiensammlung